What Does Recovery Mean to Adults who Self-injure? An interpretative Phenomenological Analysis. - Wills, Kathryn A (International Journal of Psychosocial Rehabilitation, 2013)
A paucity of research has explored the meaning or conceptualisation of recovery from the perspective of individuals who self-injure. This study used semi structured interviews to explore the meaning of recovery from the perspectives of 6 indi- viduals who self-injure, all of whom were accessing support from secondary mental health services. Factors considered to enhance or hinder the recovery process were also explored. Interpretive phenomenological analysis was used to analyse data. Analysis generated three superordinate themes: ‘the recovering self’, ‘evolving relationship with self-injury’, and ‘in- clusion vs. isolation’. Recovery was conceptualised as a multidimensional concept incorporating a broad range of intraper- sonal and interpersonal factors. Gaining control over self-injurious behaviour was regarded as an important element in re- covery, although it was not a defining feature of recovery for participants. This has implications for clinical psychology practice highlighting the danger of treatment approaches that prioritise self-injury cessation at the detriment of other indic- ators of recovery.